ANALISIS KATEGORI TINGKAT AWAL SISTEM MANAJEMAN KESEHATAN DAN KESELAMATAN KERJA (SMK3) PT. KERTA RAJASA RAYA SIDOARJO - Suherdin Suherdin (UNUSA Press, 2021)
PT. X is a multinational company that focuses on the production of plastic bags. Based on company data, shows that the annual work accident rate is still high, in 2018 there were 97 cases of work accidents. Occupational accident cases can be handled through the development of a system that regulates every activity to be safe, namely the Occupational Health and Safety Management System (OHSMS). The purpose of this study was to determine the achievement of the application of K3 in the company by analyzing the initial level criteria for implementing OHSMS based on Government Regulation Number 50 of 2012 concerning OHSMS. This research uses a quantitative approach. Based on the data collection aspect, it is included in observational research. The data analysis was conducted descriptively, to see the percentage of fulfilment of the criteria and elements at the initial level of OHSMS. The results showed that PT. X has just met 19 criteria for the initial level of OHSMS and the fulfilment of the new criteria has reached 29.68%, meaning it is included in the poor category. Based on the research results it can be concluded that PT. X has not met the initial level 64 criteria, currently, the fulfilment category is still in the low category.